Techno-economic aspects of concrete lightweighting by char enrichment with phosphates from wastewater - Josef Marousek; Beata Gavurova; Anna Marouskova; Babak Minofar (Chemical Engineering Journal Advances)
Portland cement (PC) production is a major contributor to environmental pollution due to its resource and energy – intensive nature, ranking as the 3rd largest source. Humans excrete approximately 5 g of phosphorus (P) day-1, which is often precipitated by salts into hardly applicable minerals such as struvite (in developed countries) or contributes to eutrophication (in developing countries). Worldwide, biogas plants produce a billion tons of digestate daily. Proposed solutions involve dewatering, charring and activation of digestate that is subsequently used to sorb P from wastewater and used as a PC substitute. Unique laboratory findings indicate that iron phosphates (FeP) on charred digestate can enhance concrete strength parameters (up to 80 %); reducing weight (- 18 %) and production cost (- 4 %) while turning carbon emissions into carbon sequestration. The mechanisms behind the experimental results are investigated through molecular modeling. It is revealed that interactions of char and FeP enhance aggregates, forming stronger contact ion pairs and increasing concrete strength and durability. Although the concept brings many technical, economic, and environmental improvements, further analyses are needed, especially regarding scaling up and the durability of the concrete.